Genome‐wide association study of word reading: Overlap with risk genes for neurodevelopmental disorders. (27th March 2020) - Price, Kaitlyn M.; Wigg, Karen G.; Feng, Yu; Blokland, Kirsten; Wilkinson, Margaret; He, Gengming; Kerr, Elizabeth N.; Carter, Tasha‐Cate; Guger, Sharon L.; Lovett, Maureen W.; Strug, Lisa J.; Barr, Cathy L.
Abstract: Reading disabilities (RD) are the most common neurocognitive disorder, affecting 5% to 17% of children in North America. These children often have comorbid neurodevelopmental/psychiatric disorders, such as attention deficit/hyperactivity disorder (ADHD). The genetics of RD and their overlap with other disorders is incompletely understood. To contribute to this, we performed a genome‐wide association study (GWAS) for word reading. Then, using summary statistics from neurodevelopmental/psychiatric disorders, we computed polygenic risk scores (PRS) and used them to predict reading ability in our samples. This enabled us to test the shared aetiology between RD and other disorders. The GWAS consisted of 5.3 million single nucleotide polymorphisms (SNPs) and two samples; a family‐based sample recruited for reading difficulties in Toronto (n = 624) and a population‐based sample recruited in Philadelphia [Philadelphia Neurodevelopmental Cohort (PNC)] (n = 4430). The Toronto sample SNP‐based analysis identified suggestive SNPs ( P 5 × 10 −7 ) in the ARHGAP23 gene, which is implicated in neuronal migration/axon pathfinding. The PNC gene‐based analysis identified significant associations ( P < 2.72 × 10 −6 ) for LINC00935 and CCNT1, located in the region of the KANSL2/CCNT1/LINC00935/SNORA2B/SNORA34/MIR4701/ADCY6 genes on chromosome 12q, with near significant SNP‐based analysis. PRS identified significant overlap between word reading and intelligence ( R 2 = 0.18, P = 7.25 × 10 −181 ), word reading and educational attainment ( R 2 = 0.07, P = 4.91 × 10 −48 ) and word reading and ADHD ( R 2 = 0.02, P = 8.70 × 10 −6 ; threshold for significance = 7.14 × 10 −3 ). Overlap was also found between RD and autism spectrum disorder (ASD) as top‐ranked genes were previously implicated in autism by rare and copy number variant analyses. These findings support shared risk between word reading, cognitive measures, educational outcomes and neurodevelopmental disorders, including ASD. Abstract :